Jamaica: A New Literacy Setting for Postcolonial Literature - Angela E. Rhone (HOW, 2016)
What is world literature? Who determines what constitutes world literature? How do educators begin to train prospective and current teachers who are, or who will be responsible for presenting world literature in the classroom? How do educators begin to prepare these teachers to look critically and analyze the new movement in world literature, which includes literature from postcolonial countries? What does it take to create a critical pedagogy in world literature? These are some of the questions I reflected upon as I left for Jamaica, West Indies.